Double-phase reinforced metal magnesium-based composite material as well as preparation and forming methods thereof
By adopting duplex reinforced metal magnesium-based composite materials and 3D printing technology, the problem of insufficient mechanical properties and corrosion resistance of magnesium alloys is solved, and the high-performance molding of magnesium alloys is achieved, meeting the strict requirements of aerospace and aviation products.
Patent Information
- Application Number
- CN202411851329.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
The mechanical properties and corrosion resistance of existing magnesium alloys have not met the strict requirements of the new generation of aviation and aerospace products, and their molding methods such as casting and 3D printing have problems such as looseness, pores, slag inclusion, and cracks.
The powder was prepared by ball milling, screening, drying and other processes, and molded by 3D printing technology to ensure printing in a low oxygen atmosphere to avoid oxidation.
It has achieved the improvement of mechanical properties and optimization of corrosion resistance of magnesium alloys, which can meet the strict performance requirements of aerospace and aviation products, and achieve rapid and accurate molding through 3D printing technology.
Smart Images

Figure CN119710405A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium alloys, and in particular relates to a dual-phase reinforced magnesium-based composite material and a preparation and molding method thereof. Background Art
[0002] Magnesium alloys are widely used in aviation, aerospace, new energy vehicles and other fields due to their low density, high specific strength, good casting performance and machinability. Although magnesium alloys have many excellent properties, their application fields are constantly expanding and their demand is increasing year by year, magnesium alloys are close-packed hexagonal and are mostly formed by casting processes. In order to improve the mechanical properties of magnesium alloys, rare earth elements are often added to them. However, the mechanical properties of the batch production do not exceed 320MPa, and the corrosion rate after 24 hours is about 20mg / (cm 2 ·d). Although additive manufacturing has obvious advantages in forming high-strength magnesium alloys, the mechanical properties of conventional alloys (such as AZ91D, WE43, etc.) or rare earth magnesium alloys do not exceed 350MPa, and it is difficult to meet the corrosion resistance requirements. As a result, the application of magnesium alloys and magnesium alloy additive manufacturing technology is limited.
[0003] At present, magnesium alloys are formed by casting and 3D printing. Due to factors such as a wide solidification temperature range, large solidification shrinkage, gas inhalation during the smelting process and oxide formation, poor metal liquid fluidity, inability to completely eliminate gas during the solidification process, slow casting speed, and uneven cooling, casting often causes problems such as looseness, pores, slag inclusions, and cracks. The 3D printing technology of magnesium alloys has received extensive attention in recent years. However, on the one hand, due to the rapid cooling and solidification of the molten pool during the powder bed fusion (PBF) process, the gas fails to escape in time, resulting in the formation of pores or pores. On the other hand, due to the process characteristics of layer-by-layer printing, the transition between layers may not be smooth enough, resulting in step-like defects on the surface. On the other hand, magnesium alloys are easily oxidized at high temperatures, and the formation of oxides may increase the brittleness of the material. Magnesium alloy 3D printing is very sensitive to process parameters (such as laser power, scanning speed, layer thickness, etc.). Improper parameter settings may lead to the formation of defects. Currently, the types of magnesium alloys suitable for 3D printing are limited.
[0004] In summary, the mechanical properties of magnesium alloys formed by casting or 3D printing did not exceed 350 MPa, and the corrosion rate after 24 hours was high, usually about 20 mg / (cm 2 ·d) It is difficult to meet the stringent mechanical properties and corrosion resistance requirements of the new generation of aviation and aerospace products. Therefore, it is still challenging to improve the mechanical properties and corrosion resistance of magnesium alloys. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a dual-phase reinforced magnesium-based composite material and a preparation and molding method thereof.
[0006] This is achieved specifically through the following technical solutions:
[0007] A dual-phase reinforced magnesium-based composite material comprises, by mole percentage, Mg 87.6-89.4%, Al 9.5-10.5%, Zn 0.6-1.1%, Mn 0.5-0.8%, Y 1-3%, TiC 1-5%, wherein the total mole fraction of Mg, Al, Zn and Mn is 100%.
[0008] A preparation method of a dual-phase reinforced metal magnesium-based composite material comprises the following steps: weighing magnesium powder, aluminum powder, zinc powder, manganese powder, yttrium powder and titanium carbide according to a formula amount, placing them in a ball mill, mixing and ball milling, screening and drying to obtain a dual-phase reinforced metal magnesium-based composite material.
[0009] Furthermore, the mixed ball milling is anaerobic intermittent ball milling; anaerobic means under a protective gas atmosphere.
[0010] Furthermore, the process conditions of the mixed ball milling are: the protective gas is argon, the ball-to-material ratio is (4-6): 1, the rotation speed is 60-120r / min, the ball milling time is 1.5-2.5h, and the intermittent frequency is stirring for 15-20min and then air cooling for 3-5min.
[0011] The purity of the argon gas is 99.999%.
[0012] The particle size of the dual-phase reinforced magnesium-based composite material powder is 15-63 μm.
[0013] Furthermore, the drying process conditions are: temperature of 70-100°C and time of 3-5h.
[0014] A molding method of a dual-phase reinforced magnesium-based composite material comprises the following steps:
[0015] (1) Model part drawing: Draw the 3D model of the part according to the use requirements, import the 3D model into the layered slicing software for layered slicing and adding supports, and obtain the layered slicing stl format model and support files;
[0016] Furthermore, the model parts are drawn according to the use requirements, the size requirements of the parts are determined, the parts are 3D modeled using UG modeling software, and after the 3D modeling is completed, the 3D model is exported in stl format, and after being processed by layered slicing software, it is imported into the laser selective melting molding equipment.
[0017] Furthermore, the layered slicing is to import the three-dimensional model in stl format into Magics software, first determine the arrangement of parts, and then add support and layered slicing to the model.
[0018] (2) Molding preparation:
[0019] a. Loading: Load the dual-phase reinforced magnesium-based composite material into the powder tank;
[0020] b. Assembling the substrate and the scraper: Install the magnesium alloy substrate on the movable bottom plate in the forming chamber, and then install the scraper to ensure that the substrate and the scraper are in a parallel state;
[0021] c. Filling protective gas: Fill the printing chamber with protective gas to make the oxygen content less than 80ppm;
[0022] (4) Printing: Import the layered and sliced STL format model and support files into the laser selective melting forming equipment, set the printing parameters, and start spreading powder after the substrate reaches 200-250°C. When the set powder thickness is reached, start printing.
[0023] Furthermore, the printing parameters are: laser power of 95 W, scanning speed range of 420-480 mm / s, scanning spacing of 0.05 mm, layer thickness of 0.03 mm, and the profile parameters are consistent with the forming parameters.
[0024] The molding method of the dual-phase reinforced magnesium-based composite material of the present invention is suitable for preparing aerospace products and aviation products.
[0025] Beneficial effects:
[0026] The magnesium alloy of the present invention has Mg, Al, Zn and Mn as main elemental components, Y and TiC as reinforcing materials, and is formed using 3D printing technology. It has high mechanical properties, excellent corrosion resistance, fast and precise forming, and can be used to manufacture aerospace and aviation products to meet the stringent performance requirements of aerospace and aviation products. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The SEM images of the dual-phase reinforced magnesium-based composite material powder in Example 1, wherein (a) the overall morphology; (b) the single spherical morphology;
[0028] Figure 2 is the tensile test curve of Example 1;
[0029] Figure 3 This is the tensile test curve of Example 2. DETAILED DESCRIPTION
[0030] The specific embodiments of the present invention are further described in detail below, but the present invention is not limited to these embodiments, and any improvement or substitution based on the basic spirit of the present embodiment still falls within the scope of protection required by the claims of the present invention.
[0031] Example 1
[0032] A method for preparing a dual-phase reinforced magnesium-based composite material, comprising the following steps:
[0033] (1) Powder ball milling: Magnesium powder, aluminum powder, zinc powder, manganese powder, yttrium powder and titanium carbide with a molar percentage of Mg 87.6%, Al 10.5%, Zn 1.1%, Mn 0.8%, Y3% and TiC 2% were weighed and placed in a ball mill. The powder was ball milled at a ball-to-material ratio of 5:1 and a rotation speed of 60 r / min in an Ar atmosphere with a purity of 99.999%. During the ball milling process, air cooling was required for 5 min every 15 min of stirring. The total time was 1.5 h. After the ball milling was completed, the powder with a particle size of 15-63 μm was sieved and dried at 70°C for 5 h to obtain a dual-phase reinforced magnesium-based composite material powder. The SEM image is shown in FIG. Figure 1 ;
[0034] Depend on Figure 1 It can be seen that the microstructure of the dual-phase reinforced magnesium-based composite material powder of the present invention is a spherical structure, the particle sizes are different but the sizes are all within 100 μm, the particles are evenly distributed, and the particle surface is rough;
[0035] (2) Model parts drawing: According to the use requirements, determine the size requirements of the parts, use UG modeling software to perform 3D modeling on the parts, and export the 3D model in stl format after the 3D modeling is completed. Import the 3D model in stl format into Magics software to first determine the placement of the parts, then add support and layer slices to the model to obtain the layered and sliced stl format model and support files;
[0036] (3) Molding preparation:
[0037] a. Loading: The dual-phase reinforced magnesium-based composite material powder obtained in step (1) is loaded into the powder tank;
[0038] b. Assembling the substrate and the scraper: Install the magnesium alloy substrate on the movable bottom plate in the forming chamber, and then install the scraper. During the installation of the substrate and the scraper, ensure that the substrate and the scraper are in a parallel state;
[0039] c. Filling protective gas: Fill the printing chamber with inert gas to make the oxygen content less than 80ppm;
[0040] (4) Printing: The layered and sliced stl format model and support files are imported into the laser selective melting forming equipment, and the laser power is opened in the control software and set to 95 W, the scanning speed range is 420 mm / s, the scanning interval is 0.05 mm, and the layer thickness is 0.03 mm. After the substrate is preheated to 220 °C, powder spreading begins. When the powder layer thickness is 0.03 mm, printing is started to obtain a dual-phase reinforced magnesium-based composite material, in which the contour parameters are consistent with the forming parameters.
[0041] Example 2
[0042] A method for preparing a dual-phase reinforced magnesium-based composite material, comprising the following steps:
[0043] (1) Powder ball milling: Magnesium powder, aluminum powder, zinc powder, manganese powder, yttrium powder and titanium carbide with a molar percentage of Mg 88.2%, Al 10.3%, Zn 0.8%, Mn 0.7%, Y1.3% and TiC 4.0% were weighed and placed in a ball mill. The powder was ball milled at a ball-to-material ratio of 5:1 and a rotation speed of 60 r / min in an Ar atmosphere with a purity of 99.999%. During the ball milling process, air cooling was required for 5 min every 15 min of stirring. The total time was 1.5 h. After the ball milling was completed, the powder was sieved to obtain a particle size of 15-63 μm. The powder was then dried at 80°C for 5 h to obtain a dual-phase reinforced metal magnesium-based composite material powder with a particle size of 15-63 μm. The SEM image is shown in FIG. Figure 1 ;
[0044] (2) Model parts drawing: According to the use requirements, determine the size requirements of the parts, use UG modeling software to perform 3D modeling on the parts, and export the 3D model in stl format after the 3D modeling is completed. Import the 3D model in stl format into Magics software to first determine the placement of the parts, then add support and layer slices to the model to obtain the layered and sliced stl format model and support files;
[0045] (3) Molding preparation:
[0046] a. Loading: The dual-phase reinforced magnesium-based composite material powder obtained in step (1) is loaded into the powder tank;
[0047] b. Assembling the substrate and the scraper: Install the magnesium alloy substrate on the movable bottom plate in the forming chamber, and then install the scraper. During the installation of the substrate and the scraper, ensure that the substrate and the scraper are in a parallel state;
[0048] c. Filling protective gas: Fill the printing chamber with inert gas to make the oxygen content less than 80ppm;
[0049] (4) Printing: The layered and sliced stl format model and support files are imported into the laser selective melting forming equipment, and the laser power is opened in the control software and set to 95W, the scanning speed range is 450mm / s, the scanning interval is 0.05mm, and the layer thickness is 0.03mm. After the substrate is preheated to 210℃, powder spreading begins. When the powder layer thickness is 0.03mm, printing is started to obtain a dual-phase reinforced metal magnesium-based composite material, in which the contour parameters are consistent with the forming parameters.
[0050] Example 3
[0051] A method for preparing a dual-phase reinforced magnesium-based composite material, comprising the following steps:
[0052] (1) Powder ball milling: Magnesium powder, aluminum powder, zinc powder, manganese powder, yttrium powder and titanium carbide with molar percentages of Mg 89.4%, Al 9.5%, Zn 0.6%, Mn 0.5%, Y 1.0% and TiC 1.0% were weighed and placed in a ball mill. The powder was ball milled at a ratio of 5:1 to powder and a rotation speed of 60 r / min in an Ar atmosphere with a purity of 99.999%. During the ball milling process, air cooling was required for 5 min after stirring for 15 min. The total time was 1.5 h. After the ball milling was completed, the powder was sieved to obtain a particle size of 15-63 μm. The powder was then dried at 100° C. for 5 h to obtain a dual-phase reinforced magnesium-based composite material powder with a particle size of 15-63 μm. The SEM image is shown in FIG. Figure 1 ;
[0053] (2) Model parts drawing: According to the use requirements, determine the size requirements of the parts, use UG modeling software to perform 3D modeling on the parts, and export the 3D model in stl format after the 3D modeling is completed. Import the 3D model in stl format into Magics software to first determine the placement of the parts, then add support and layer slices to the model to obtain the layered and sliced stl format model and support files;
[0054] (3) Molding preparation:
[0055] a. Loading: The dual-phase reinforced magnesium-based composite material powder obtained in step (1) is loaded into the powder tank;
[0056] b. Assembling the substrate and the scraper: Install the magnesium alloy substrate on the movable bottom plate in the forming chamber, and then install the scraper. During the installation of the substrate and the scraper, ensure that the substrate and the scraper are in a parallel state;
[0057] c. Filling protective gas: Fill the printing chamber with inert gas to make the oxygen content less than 80ppm;
[0058] (4) Printing: The layered and sliced stl format model and support files are imported into the laser selective melting forming equipment, and the laser power is opened in the control software and set to 95 W, the scanning speed range is 480 mm / s, the scanning interval is 0.05 mm, and the layer thickness is 0.03 mm. After the substrate is preheated to 245 °C, powder spreading begins. When the powder layer thickness is 0.03 mm, printing is started to obtain a dual-phase reinforced metal magnesium-based composite material, in which the contour parameters are consistent with the forming parameters.
[0059] The mechanical properties test results of the dual-phase reinforced magnesium-based composite materials obtained in Examples 1-3 are shown in Table 1. The test curves are shown in Figure 2 and Figure 3 As shown;
[0060] Table 1 Mechanical properties test results of various embodiments
[0061] sample Tensile strength(MPa) Yield strength(MPa) Elongation(%) Example 1 422.05 318.17 3.8 Example 2 430.01 313.67 4.2 Example 3 426.07 317.35 3.9
[0062] The dual-phase reinforced magnesium-based composite material parts in Example 2 were immersed in 0.06 mol / L NaCl solution. After the sample was immersed in the NaCl solution for 24 hours, the corrosion rate reached a maximum value of about 10.5 mg / (cm 2 ·d), as the immersion time of the sample in the salt solution continues to increase, the corrosion rate gradually slows down. The statistical results of the corrosion rate changing with the immersion time are shown in Table 2 below.
[0063] Table 2 Corrosion rate change detection results
[0064] Serial number Time <![CDATA[Corrosion rate mg / (cm 2 ·d)]]> 1 24 10.5 2 48 8.6 3 72 7.4 4 96 6.8 5 120 6.5
[0065] In the specific implementation process of the present invention, the magnesium alloy substrate is installed on the movable bottom plate in the forming chamber, and then the scraper is installed. During the installation process, the substrate and the scraper are ensured to be basically in a parallel state to ensure that a uniform and consistent powder layer can be obtained in the subsequent powder spreading process.
[0066] In the specific implementation process of the present invention, high-purity argon is used as the inert gas. When the printing chamber is filled with the inert gas, oxygen is also pumped out to ensure that the oxygen content in the printing chamber is less than 80ppm to prevent unexpected factors from occurring during the printing process.
[0067] In the specific implementation process of the present invention, the base is preheated and the preheating temperature is reasonably controlled, which can effectively reduce the residual stress level of the alloy, that is, reduce the risk of cracking.
Claims
1. A dual-phase reinforced magnesium-based composite material, characterized in that: The dual-phase reinforced magnesium-based composite material powder comprises, by mole percentage, Mg 87.6-89.4%, Al 9.5-10.5%, Zn 0.6-1.1%, Mn 0.5-0.8%, Y1-3%, and TiC 1-5%, wherein the total mole fraction of Mg, Al, Zn, and Mn is 100%.
2. The method for preparing a dual-phase reinforced magnesium-based composite material according to claim 1, characterized in that: Specifically, magnesium powder, aluminum powder, zinc powder, manganese powder, yttrium powder and titanium carbide are weighed according to the formula amount and placed in a ball mill, and mixed and ball-milled, sieved and dried to obtain a dual-phase reinforced metal magnesium-based composite material.
3. The method for preparing a dual-phase reinforced magnesium-based composite material according to claim 2, characterized in that: The mixed ball milling is an anaerobic intermittent ball milling; the process conditions of the mixed ball milling are: the protective gas is argon, the ball-to-material ratio is (4-6): 1, the rotation speed is 60-120r / min, the ball milling time is 1.5-2.5h, and the intermittent frequency is stirring for 15-20min and then air cooling for 3-5min.
4. The method for preparing a dual-phase reinforced magnesium-based composite material according to claim 2, characterized in that: The particle size of the dual-phase reinforced magnesium-based composite material powder is 15-63 μm.
5. The method for preparing a dual-phase reinforced magnesium-based composite material according to claim 2, characterized in that: The drying process conditions are as follows: temperature is 70-100° C. and time is 3-5 hours.
6. The molding method of a dual-phase reinforced magnesium-based composite material according to claim 1, characterized in that: The steps include: (1) Model part drawing: Draw the 3D model of the part according to the use requirements, import the 3D model into the layered slicing software for layered slicing and adding supports, and obtain the layered slicing stl format model and support files; (2) Molding preparation: a. Loading: Load the dual-phase reinforced magnesium-based composite material into the powder tank; b. Assembling the substrate and the scraper: Install the magnesium alloy substrate on the movable bottom plate in the forming chamber, and then install the scraper to ensure that the substrate and the scraper are in a parallel state; c. Filling protective gas: Fill the printing chamber with protective gas to make the oxygen content less than 80ppm; (4) Printing: Import the layered and sliced STL format model and support files into the laser selective melting forming equipment, set the printing parameters, and start spreading powder after the substrate reaches 200-250°C. When the set powder thickness is reached, start printing.
7. A molding method for a dual-phase reinforced magnesium-based composite material according to claim 6, characterized in that: The model parts are drawn according to the use requirements, the size requirements of the parts are determined, the parts are 3D modeled using UG modeling software, and after the 3D modeling is completed, the 3D model in stl format is exported and imported into the laser selective melting molding equipment after being processed by layered slicing software.
8. The molding method of a dual-phase reinforced magnesium-based composite material according to claim 6, characterized in that: The layered slicing is to import the three-dimensional model in stl format into Magics software, first determine the arrangement of parts, and then add support and layered slicing to the model.
9. A molding method for a dual-phase reinforced magnesium-based composite material according to claim 6, characterized in that: The printing parameters are as follows: laser power is 95 W, scanning speed range is 420-480 mm / s, scanning spacing is 0.05 mm, layer thickness is 0.03 mm, and contour parameters are consistent with forming parameters.